The Relationship Between Parents' Attention And The Emotional Development Of Early Childhoods In The Ujung Gurun Village, Padang City - Fandi Ahmad Zikri; Solfema Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research starts from the lowest emotional development of early childhood in the Ujung Gurun Village, Padang City. One of the contributing factors is the apparent lack of parental attention from early childhood parents. The purpose of this activity is to describe parental attention and emotional development of early childhood and also to see the relationship between parental attention and emotional development of early childhood in Ujung Gurun Village, Padang City. The approach used in this study is quantitative with a correlational approach. The total population is 32 people who are parents of early childhood while the sample is 10 people. The sampling method used is the stratified random sampling method. The data collection technique used is a questionnaire and the tool is in the form of a questionnaire. The data analysis technique used is product moment. The results of the study found that parents' attention was low and it was also seen that the emotional development of early childhood was included in the low category. A significant relationship was found between parental attention and early childhood emotional development. Suggestions are expected for parents to be able to improve the emotional development of early childhood through the attention given.